Climate change and colonialism in the Green Economy: Book review of Magdalena Heuwieser's "Green Colonialism in Honduras: Land Grabbing in the Name of Climate Protection and the Defense of the Commons" (Alternautas, 2015)
Magdalena Heuwieser’s Green Colonialism in Honduras: Land Grabbing in the name of climate protection and the defence of the commons looks closely into one of the countries most affected by climate change. Through the lens of a decolonial theory developed in Latin America, this German-language book provides a profound and often shocking analysis of how supposedly ‘green’ projects are hijacked by more powerful political and economic interests. But it goes beyond an account of a few failed or mismanaged climate change initiatives to show how the ‘Green Economy’ fails to solve the multiple environmental, financial and food crises Honduras, and the world, face today. It is this political ecology analysis of climate change action and development that may be the most valuable contribution of this book. Heuwieser (re)defines them as part of a struggle over territory, resources and power and provides an alternative mini manifesto for the defence of the commons. This book should be mandatory reading for anyone interested in the region, let alone those planning climate change or development projects there.